The effect of using instructional computer on the academic achievement of students in the fourth grade in the natural sciences subject - BOUTEBAL, Saadeddine; BENKHELIFA, Fatima (Journal of Human Sciences, 2020)
This study aimed to discover the effect of the use of instructional computer on the academic achievement of students in the fourth grade in the natural sciences subject For this purpose, the descriptive and semi-experimental approach based on the single group design was adopted,   the sample of study consisted of 38  students. An achievement test was applied in this study before and after the treatment. The results of the study showed that there were statically significant differences in achievement  in favor of the second phase, and that there were no statically significant difference due to gender.